Patents for Environmentalists - F. Scott Kieff (Washington University Journal of Law & Policy, 2002)
The patent system may be good for environmentalists because it increases public access to new technologies, decreases use of environmentally dangerous self-help approaches, and increases the wealth available for all purposes, including helping the custodians of biodiversity. To the extent new technologies are helpful to environmental goals, such as cleaner burning engines, the patent system can be seen as generating environmental good by providing incentives for their commercialization ex ante. To the extent new technologies are harmful to environmental goals, such as poisonous chemicals, the patent system can be seen as at least not causing environmental damage because the patent right to exclude use would not interfere with a regulatory system’s own effort to exclude use. To the extent environmentalists are concerned about ex post ability to gain access to technologies covered by a patent right to exclude use, the patent system’s rules about licensing and price discrimination encourage patentees to seek out and license as many users as possible, even low value users. Moreover, to the extent environmentalists are concerned about dangerous self-help approaches, such as the terminator technologies that might be used by sellers of agricultural products, the patent system provides these sellers with a more attractive option that also poses less potential danger for the environment. Finally, to the extent environmentalists are concerned about helping custodians of biodiversity, the patent system creates economic wealth from such biodiversity that is then available for allocation among its custodians and users according to ordinary market and political mechanisms. Therefore, those who care about the environment ought to care about patents precisely because the present patent system may be so beneficial for the environment.
Keywords: Environmentalism; Patents; Environmental protection; Patent law; United States